2014
DOI: 10.1016/j.ijpharm.2014.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations into the influence of the position of a breaking line on the tensile failure of flat, round, bevel-edged tablets using finite element methodology (FEM) and its practical relevance for industrial tablet strength testing

Abstract: were studied. FEM results obtained for fully elastic and elasto-plastic tablets were 22 fairly similar, but they highlighted large differences in stress distributions depending 23 on the position of the breaking line. The stress values at failure were predicted to be 24 similar for tablets tested at an angle of 45° or above, whereas at lower test angles the 25 predicted breaking loads were up to 3 times larger. The stress distributions 26 suggested that not all breaking line angles would result in clean tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Similar effects, but more detailed due to the use of different breaking line positions in terms of angles relative to the loading plane, were found using FEM (Podczeck et al, 2014), and their theoretic work also predicted that not all breaking line angles would result in clean tensile failure. The practical results, however, only confirmed some deviations from a clean tensile failure due to the position of the breaking line, whereas the breaking forces as such were only marginally affected by the position of the breaking line relative to the loading plane.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Similar effects, but more detailed due to the use of different breaking line positions in terms of angles relative to the loading plane, were found using FEM (Podczeck et al, 2014), and their theoretic work also predicted that not all breaking line angles would result in clean tensile failure. The practical results, however, only confirmed some deviations from a clean tensile failure due to the position of the breaking line, whereas the breaking forces as such were only marginally affected by the position of the breaking line relative to the loading plane.…”
Section: Introductionmentioning
confidence: 54%
“…The load was kept constant for all models. Similar to previous work (Podczeck et al, 2013(Podczeck et al, , 2014 only one linear elastic model with the properties of Araldite CT200, hardened with 30% w/w Hardener 901, for which Young's modulus of elasticity (2.58 GPa) and Poisson's ratio (0.35) were taken from the literature (Burger, 1969), was studied. The theory of elasticity (Timoshenko and Goodier, 1987) predicts that relative stress distributions are independent of Young's modulus and Poisson's ratio, and that this holds in FEM studies has previously been confirmed Heasley, 2013, Podczeck et al, 2013).…”
Section: Fem Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations